A universal rate-dependent damping model for arbitrary damping-frequency distribution. (15th March 2022) - Tian, Yuan; Fei, Yifan; Huang, Yuli; Lu, Xinzheng
Highlights: A damping model for arbitrary damping-frequency distribution is proposed. The elemental damping is implemented in an open-source software (OpenSees). The relative error of damping compared with experimental results is within 6%. Abstract: Damping is fundamental to structural dynamics. Reasonable damping models facilitate accurate and reliable dynamic analyses of damped structures. Existing experiments indicate that damping is dependent but not proportional to the frequency. Hence, it may be challenging for viscous and rate-independent damping models to accurately simulate the frequency characteristics. This study proposes a universal rate-dependent damping model and its implementation in an open-source finite-element analysis software, OpenSees. A comparison with experimental results verify that the proposed damping model can accurately and flexibly simulate the distribution of damping energy dissipation in various frequency domains wherein the relative error of the damping is significantly smaller than that of the widely used classical damping models.